Analytical Insights into Methods for Measuring Ischemia-Modified Albumin - Stefano Zoroddu; Angelo Zinellu; Ciriaco Carru; Salvatore Sotgia (Molecules, 2024)
Ischemia-modified albumin (IMA) has emerged as a pivotal biomarker for the early detection of ischemic conditions, particularly myocardial ischemia, where timely diagnosis is crucial for effective intervention. This review provides an overview of the analytical methods for assessment of IMA, including Albumin Cobalt Binding (ACB), Albumin Copper Binding (ACuB), Enzyme-Linked Immunosorbent Assay (ELISA), new techniques such as liquid crystal biosensors (LCB), quantum dot coupled X-ray fluorescence spectroscopy (Q-XRF), mass spectrometry (MS), and electron paramagnetic resonance (EPR) spectroscopy. Each method was thoroughly examined for its analytical performance in terms of sensitivity, specificity, and feasibility. The ACB assay is the most readily implementable method in clinical laboratories for its cost-effectiveness and operational simplicity. On the other hand, the ACuB assay exhibits enhanced sensitivity and specificity, driven by the superior binding affinity of copper to IMA. Furthermore, nanoparticle-enhanced immunoassays and liquid crystal biosensors, while more resource-intensive, significantly improve the analytical sensitivity and specificity of IMA detection, enabling earlier and more accurate identification of ischemic events. Additionally, different biological matrices, such as serum, saliva, and urine, were reviewed to identify the most suitable for accurate measurements in clinical application. Although serum was considered the gold standard, non-invasive matrices such as saliva and urine are becoming increasingly feasible due to advances in technology. This review underscores the role of IMA in clinical diagnostics and suggests how advanced analytical techniques have the potential to significantly enhance patient outcomes in ischemic disease management.